‘Fish’ and ‘Non-Fish’ in Lio and Nage: Folk-Intermediates and Folk-Generics in the Fish Classification of Two Eastern Indonesian Peoples - Forth, Gregory (Ethnobiology Letters, 2017)
Based on recent field research on Flores Island, this paper describes the classification of fish found among the Lio people. Formally, Lio fish taxonomy closely resembles that of the Nage of central Flores, discussed in a previous paper (Forth 2012), but differs insofar as several kinds of freshwater fish, all members of the Gobioidei, are subsumed in a named folk-intermediate taxon labeled mbo. Most attention is given to Lio names for folk-generics included in this intermediate. These correspond to the same species and genera included in a Nage folk-intermediate which, however, is unnamed. Moreover, Lio names for the component generics are clearly motivated by the same morphological and behavioral features as are reflected in Nage names for the same generics, yet the Lio names themselves are lexically quite different. These simultaneous classificatory similarities and nomenclatural differences are discussed with reference to the parts played by a common cultural heritage and natural discontinuity in the categorization of fish among these two ethno-linguistically related groups.